Gender dynamics in the biofortified bean value chain in Burundi - Nchanji, Eileen; Nduwarugira, Eric; Ndabashinze, Blaise; Ntukamazina, Nepomuscene; Toywa, Johnworker; Lutomia, Cosmas Kweyu (SAGE Publications, 2023)
Biofortified beans are being promoted in Burundi to solve malnutrition issues among rural households. The study was conducted in Muyinga and Gasorwe communes, where biofortified bean varieties were disseminated. This study aims to understand gender roles and practices in households and farms and how these roles and practices influence participation and uptake of biofortified beans. Lastly, it looks at the role of extension in increasing the uptake of agricultural technologies like biofortified bean varieties. Data were collected using a mixed-method approach—focus group discussions, key informant interviews and questionnaires and analyzed using content analysis, descriptive statistics, and a probit model on STATA software. Descriptive results indicated increasing joint farm management and decision-making on bean production, with men taking the lead in markets and income accrued from the sale of crops. Despite the promotion of various improved bean varieties, only two biofortified bean varieties, MAC44 and RWR2245, were adopted by smallholder farmers. The probit results indicated that utilization of hired labor, the source of biofortified improved bean seed, total cultivated land area, decision-maker on land use, years after the first adoption, and the type of extension services sought were significant factors that influenced farmers’ use of biofortified beans varieties. Based on the study's findings, more effort is required to promote access to inclusive extension services, market and decision-making on income accrued from the sale of farm produce.